Hello,
You cannot write it unless x is a positive integer.x = 1 + 1 + ... + 1 (x times)
Hello all,
This is a differentiaiton question given to me by my friend.I could not find the mistake in the proof.
x = x
x = 1 + 1 + ... + 1 (x times)
multiplying by x
x(x) = x(1 + 1 + ... + 1)
x2 = x + x + ... + x
D(x2) = D(x + x + ... + x)
D(x2) = D(x) + D(x) + ... + D(x)
2x = 1 + 1 + ... + 1 (x times)
2x = x
2 = 1
i think it is somewhere in the differentiation .But couldnot get it.
i hope i have not made a mistake by posting in the wrong forum.